Restoration and the City: The Role of Public Urban Squares - San Juan, César; Subiza-Pérez, Mikel; Vozmediano, Laura (Frontiers in Psychology, 2017)
Over recent decades, the study of psychological restoration has attracted a considerable amount of interest within and without the boundaries of environmental psychology, with most of the work focused on analyzing restoration in natural contexts. However, little attention has been paid to the (possible) restorative potential of urban settings, as they have usually been expected not to be restorative and to present some elements that might imply negative health outcomes in the short and long term. In this field study, our aim was to evaluate restoration in urban squares. To this end, we measured participants’ attentional and affective states both before and after spending half an hour in an urban square. A sample of 46 subjects contemplated and walked through one of the two selected squares that differed in restorative potential (PRS). Analyses revealed a statistically significant increase in cognitive performance and a decrease in negative affect in both squares. They also showed that participants reported greater stress recovery rates in one of the settings. These results support the idea that cities can be potentially restorative and justify the relevance of a research area focused on the urban designs, which may offer psychological benefits to urban citizens.